Carbon emission governance and public health efficiency in transitional China: Regional differences and spatial aggregation - Yiwen Wei; Lingxiao Guo; Qunshan Tao; Hua Wei (PLoS ONE, 2026)
Background With the coordinated advancement of China’s “dual carbon” goals and the Healthy China strategy, the harmonious development of carbon emission governance and public health service efficiency has emerged as a central issue in China’s sustainable transition. Methods This study takes 31 provincial-level administrative units in China over the period 2012–2023 as the unit of analysis, and constructs a systematic analytical framework encompassing “measurement–coupling–inequality decomposition–determinant identification.” Specifically, the entropy weight method is employed to assess the composite level of carbon emission governance; the DEA-SBM model is applied to evaluate public health service efficiency; the coupling coordination degree model is used to quantify the coordinated development level of the two systems; the Dagum Gini coefficient decomposition is then utilized to identify the sources of regional disparities; the Global Moran’s Index is adopted to track the evolution of spatial agglomeration; and a two-way fixed effects Tobit model is constructed to identify associated factors. Results The national coupling coordination degree (CCD) exhibited an overall trajectory of initial fluctuation followed by a sustained upward trend. During 2012–2017, the CCD of most provinces remained within the range of 0.44–0.63, rising broadly to the 0.54–0.72 interval after 2018. Inter-regional inequality consistently constituted the dominant source of total disparity throughout the study period. After 2018, the coordination gap between eastern and western regions continued to widen, while intra-regional disparities among western provinces simultaneously intensified, with both trends jointly driving an increasingly pronounced pattern of regional divergence. The Global Moran’s Index rose from 0.227 to 0.497, indicating a continuous strengthening of spatial agglomeration. The associated factors exhibited significant regional heterogeneity: R&D investment intensity demonstrated a significant positive association with CCD in central and western regions; urban population density exerted a significant inhibitory effect on coordination degree in western provinces; and the direction of the association between economic development level and CCD was opposite in eastern and central regions. Conclusions Institutional time lags, factor endowment disparities, and spatial polarization mechanisms constitute the core structural barriers constraining the coordinated development of the two systems. There is an urgent need to establish a differentiated, region-specific, and phase-based policy intervention framework to promote balanced and coordinated regional development.